Galactose therapy reduces proteinuria in patients with recurrent focal segmental glomerulosclerosis after kidney transplantation. (March 2015) - Robson, Kate; Hill, Prudence; Langsford, David; Dwyer, Karen; Goodman, David; Langham, Robyn
Abstract: Primary focal segmental glomerulosclerosis is an important cause of end‐stage kidney disease with a high rate of recurrent disease after kidney transplantation. Current therapy achieves remission in only half of patients. Recent interest has focused on the potential role of galactose in binding and inactivating the putative circulating permeability factor, supported by in vitro and clinical case report studies. Orally active and without major adverse effects, galactose has a favourable treatment profile compared with current immunosuppressive treatment options. We describe our experience using galactose therapy in two patients with recurrent focal segmental glomerulosclerosis after renal transplantation. Galactose was associated with symptomatic improvement and stabilization of graft function in one case; the other case was complicated by concurrent malignancy. In both cases, we observed a marked reduction in proteinuria with galactose treatment.